Blueprint technology: Automatic Dishwasher / Samihah Mohamad Yusoff… [et al.] - Mohamad Yusoff, Samihah; Hasan, Nur Afifah; Mohd Rashid, Nur Liana; Tuan Mohd Ariffin, Nik Izati Bayani; Zu, Shahida (2020)
SaRose Sdn. Bhd. Was created in 2020 and we proudly to present our new product that have been innovate from existing product with more powerful and function. The innovation is mainly about advance modified version of dishwasher. Dishwasher is one of the tool that are necessary and widely used among all people especially kitchen’s staff, housewife, students and others. Dishwasher is one of tool that must have in every house. Knowing this, we discover that dishwasher is one of tools that can be easily commercially in our country. Automatic Dishwasher is unique, affordable, compatible and user-friendly. Automatic Dishwasher also easy to carry since it is light and can be carried anywhere. Since there is place to refill detergent in Automatic Dishwasher so it is easy for everyone to make sure that their dishes keep clean whenever and anywhere they go. Another innovation that added on the Automatic Dishwasher is thicker of sponge, which is sponge is thicker that will enable to clean dishes more clean. For the pricing, the material cost to produce Automatic Dishwasher is RM88.00. The pricing that we include in the marker is RM150.00 including the price the worker’s overhead cost and other expenses to produce my product. However, to maximize the customers, the company carefully choose the lowest price that and the finest quality of my material from supplier. Since dishwasher is necessary things so my target market size is restaurant’s owner, housewife, students and also Malaysia’s residents. By introducing Automatic Dishwasher, it is surely will get attention in market and can compete with others bigger companies. Moreover the existing and the growth of social media will be platform to SaRose Sdn.Bhd to promote my new product. Automatic Dishwasher was produced to solve the problems for those that have problem to clean dishes manually or for those that need to do work faster so this product was innovated to help all consumer to do work quickly with the bombastic outcomes. Hence, i really sure that Automatic Dishwasher have a potential in market and will helps our company overcome any consequences as entrepreneurs in order to make my product is last longer and durable compare to other product